Investigation on mutual traveling influences between the draft tube and upstream components of a Francis turbine unit. (December 2020) - Muhirwa, Alexis; Li, Biao; Su, Wen-Tao; Liu, Quan-Zhong; Binama, Maxime; Wu, Jian; Cai, Wei-Hua
Abstract: Owing to an inconsistent load demand, hydraulic turbines are often operated under off-load range. Resultant flow instabilities comprise low-frequency pressure fluctuations, which are dependent on the operating condition and unavoidable high-frequency fluctuations evolving from the interactional design concept of hydrofoils. Through the analysis of averaged flow parameters within the runner, this article investigates the mechanism of reciprocity in flow instabilities between draft tube and upstream components. Two recommended operating conditions are used to approximate harmless traveling disturbances, and two part-load discharges are discussed accordingly. The CFD commercial code ANSYS CFX has been used for unsteady flow simulation, where the Shear Stress Transport (SST) turbulence model has been adopted. The used numerical scheme has been validated through experiments in terms of pressure pulsation characteristics, and findings display a good agreement. It has been found that low-frequency disturbances, as instabilities taking source from the fluid structure itself, can override strong flow gradients and exert a higher backward influence farther than high-frequency perturbations. The low-frequency component and its harmonic strengthened by the wall impact feedback are less sensitive to the backward damping. The blade passing frequency dominates the draft tube inlet to influence the local pressure recovery; but it is rapidly diffused and tapped by the low-frequency core instability. Highlights: The averaged runner flow predicts the reciprocity between components instability. Optimal operations define harmless distribution of traveling instabilities. The vortex rope overpowers rotor-stator interactions in remote flow excitations. Inlet cone impact is critical for the backward propagation and pressure recovery. The core activity and cone impact intensity govern admitted cone instability.